(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Current. Flatfoot is widespread in the pediatric population, this pathology reduces the cushioning function of the arch of the foot, disrupts the biomechanics of the musculoskeletal system and in the long term leads to systemic complications - rapid fatigue in medical activities, shift of the body’s center of gravity, loss of "plasticity" of gait, limitation of supination in the ankle joint, postural imbalance in the spine (hyperlordosis, kyphosis, scoliotic state) and withdrawal from sports/motor activities; Traditional measures (physical therapy, massage, supinator, plaster) are often limited to mechanical manipulation and have no effect on disorders in connective tissue metabolism. As a result, by the age of 8-14, the bone and ligament apparatus “stabilizes”, and the clinical effectiveness of correction decreases; in this context, it is necessary to introduce a protocol combining integral screening, metabolic target-oriented correction and step-by-step mechanical correction from an early age (especially the “biomechanical window” of 4-7 years).